2008
DOI: 10.1080/19320240802244025
|View full text |Cite
|
Sign up to set email alerts
|

Do Farm-to-School Programs Make a Difference? Findings and Future Research Needs

Abstract: Farm-to-school programs are increasing in number across the United States, yet research and evaluation of programs is limited, with only a few studies published in refereed journals. For this article we

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
149
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(151 citation statements)
references
References 10 publications
2
149
0
Order By: Relevance
“…Some programs have resulted in reduced health risk behaviours (including antisocial behaviour and willingness to try new foods), increased nutritional and eco-literacy, improved eating habits, increased satisfaction with life, increased emotional wellbeing, increased student resilience, better learning outcomes [129,130]. Mixed results from these programs have been documented in the literature, however studies did frequently find that the most effective program uptake was at schools where a whole-school and committed approach (with enthusiastic role modelling) was taken [33,[126][127][128][129][130][131]. It is important to note that significant constraints in study design and methodology limit comparative analysis and hence program design.…”
Section: Implications For Future Generationsmentioning
confidence: 83%
See 2 more Smart Citations
“…Some programs have resulted in reduced health risk behaviours (including antisocial behaviour and willingness to try new foods), increased nutritional and eco-literacy, improved eating habits, increased satisfaction with life, increased emotional wellbeing, increased student resilience, better learning outcomes [129,130]. Mixed results from these programs have been documented in the literature, however studies did frequently find that the most effective program uptake was at schools where a whole-school and committed approach (with enthusiastic role modelling) was taken [33,[126][127][128][129][130][131]. It is important to note that significant constraints in study design and methodology limit comparative analysis and hence program design.…”
Section: Implications For Future Generationsmentioning
confidence: 83%
“…It is important to note that significant constraints in study design and methodology limit comparative analysis and hence program design. Successful implementation and longevity of such programs (with schools often finding them hard to maintain and costly) are extremely difficult to measure, so have only started being conducted widely [127]. Generally, however, researchers agree that these programs often make a difference for the least food literate children and therefore where there is greatest need [128,131].…”
Section: Implications For Future Generationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other evaluation studies found a positive effect on attitude in the short or longer term (19,31,36,37) . In a review of Contento et al (38) , it is stated that effects of school-based nutrition education programmes on attitudes were generally positive but inconsistent.…”
Section: Reflection On the Resultsmentioning
confidence: 99%
“…Furthermore, although often limited to self-reported consumption, students in school districts across the U.S. have described a preference for fruits or vegetables after participating in FTS programs (Bontrager Yoder, Liebhart, McCarty, Meinen, Schoeller, Vargas, & LaRowe, 2014;Powers et al, 2011). Joshi, Azuma, and Feenstra (2008) reviewed findings of the effects of FTS and found that several studies showed positive effects on student food choice and attitudes and especially on increased participation in school meals, although they called for more research to determine the sustainability of the behavior change.…”
mentioning
confidence: 99%